Figure sculpting. Volume I - Faraut, Philippe; Faraut, Charisse (Honeoye, N.Y. : PCF Studios, 2013)
"Philippe and Charisse Faraut present a comprehensive approach to the complex subject of the human figure. Over 700 photos and illustrations are used to demonstrate series of exercises for the head, torso, arms, hands, legs, feet and full figure that promote rapid progress while learning the anatomy specifically relevant to the 3D artist. The traditional clay sculptor, as well as the digital sculptor, will find information on structure, planes, balance and the subtle details that are required in order to master this art. Further features include: small to life-size sculpture studies, step-by-step demonstrations, explanations for rhythm lines and S curves, illustrations for bones and muscles, numerous examples of sculpted hands and feet along with firing and finishing techniques."--Amazon.
Inception --The head and neck --The torso --The arm and shoulder --The hand --The leg --The foot --The figure --Finishing.
Includes bibliographical references and index.
Keywords: Figure sculpture -- Technique; Modeling -- Technique